Energy and economic assessment of building integrated photovoltaic (BIPV) with ev charging in tropical, maritime temperate and humid continental climates - Khan, Sanjay (2024)
The construction and transportation industries are major polluters, facing challenges from rapid development and high energy consumption. Buildings alone account for over a third of global energy use and over 36% of emissions. This research explores a potential solution: integrating Building-Integrated Photovoltaic (BIPV) systems with EV charging infrastructure. By examining BIPV designs in diverse climates like Tropical Pahang, Malaysia, Maritime temperate Canberra, Australia and Humid continental Örebro, Sweden, the study investigates optimizing these systems for different locations to achieve net-zero buildings and meet household energy needs. The research gathered data on house type, roof slope, household energy consumption, commute distance, and vehicle type from each location. The PV system size was tailored to meet net-zero targets using this diverse input data. The methodology estimated daily energy demand for households and EV charging to size the BIPV system and evaluate energy, economic, and environmental parameters. Results showed BIPV systems with EV charging could reduce energy costs, improve economics, and lower emissions towards achieving net-zero. In tropical Malaysia, a 5.6kWp grid-connected BIPV system met daily energy needs year-round, with excess energy available for grid injection. In Sweden, a 10kWp system was insufficient during harsh winters but generated excess energy in summer. Bifacial PV panels increased energy production by 10% compared to monofacial panels. In Australia, a 5kWp BIPV system met daily energy demand except in winter, with annual energy generation exceeding consumption, resulting in positive cash flow. Economically, all systems had a net positive value over their lifetime, influenced by local policies. Malaysia's net cash flow was estimated at 13,000 USD, while Sweden and Australia had 45,389 USD and 24,400 USD, respectively. Environmentally, the BIPV system with EV charging infrastructure saved 137,321 kgCO2e in Malaysia, 160,198 kgCO2e in Australia, and 44,317 kgCO2e in Sweden due to its lower emission factors.